Statistical Postprocessing of Ensemble Forecasts - Vannitsem, Stéphane; Wilks, Daniel S; Messner, Jakob (Elsevier, 2018)
This volume brings together chapters contributed by international subject-matter experts describing the current state of the art in the statistical postprocessing of ensemble forecasts. It illustrates the use of these methods in several important applications including weather, hydrological and climate forecasts, and renewable energy forecasting.